Protocol for detecting nutrient uptake and photosynthate partitioning in rice seedling using a non-invasive system - Jinzhi Li; He Zhang; Jianming Gao (STAR Protocols)
Summary: A non-invasive system can measure nutrient uptake and photosynthate partitioning simultaneously while allowing organisms to metabolize without interference in the process of measurement. Here, we present a protocol for detecting nutrient uptake and photosynthate partitioning in rice seedling using a non-invasive system. We describe steps for preparing plant material and material for the non-invasive system. We then detail procedures for setting up and applying the non-invasive measurement system.For complete details on the use and execution of this protocol, please refer to Li et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.